IMPLEMENTASI P5 (PROJEK PENGUATAN PROFIL PELAJAR PANCASILA) PADA KURIKULUM MERDEKA BELAJAR DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM - Safitri, Rida Echa; Rahim, Abdul (Kwangsan: Jurnal Teknologi Pendidikan, 2023)
In the academic year 2022/2023, the Indonesian government ratified and commenced the implementation of a new curriculum resulting from the refinement of the previous curriculum, namely the "Merdeka Belajar" curriculum. The "Merdeka Belajar" curriculum was developed to be more flexible, focusing on essential content, character development, and competencies. Within the Pancasila Student Profile Strengthening Project (P5) in the "Merdeka Belajar" Curriculum, there is a project-based extracurricular activity designed to reinforce efforts in achieving competencies and character traits according to the Pancasila student profile, formulated based on graduation competency standards. With the introduction of this new program, a review is needed regarding the implementation results of P5 from the perspective of specific subjects, namely natural sciences. For example, the implementation of P5 at MTs Negeri 2 Jember is still considered unfamiliar and has recently been enforced. Through observation, event monitoring, and interviews with relevant parties, the expected results are anticipated to be beneficial for subsequent learning. All stages have been executed successfully, leading to the conclusion that this community service activity has effectively enhanced the competence of teachers in carrying out the Pancasila student profile strengthening project. The project encompasses understanding, design, documentation, reporting, as well as evaluation and follow-up actions with satisfactory outcomes.  AbstrakPada tahun ajaran 2022/2023 pemerintah Indonesia mengesahkan dan mulai memberlakukan kurikulum baru hasil pengembangan dari penyempurnaan dari kurikulum sebelumnya yakni kurikulum merdeka belajar. Kurikulum merdeka belajar ini dikembangkan sebagai kurikulum yang lebih fleksibel, berfokus pada materi esensial, pengembangan karakter, dan kompetensi. Dalam Projek penguatan profil pelajar pancasila (P5) dalam Kurikulum Merdeka belajar adalah kegiatan kokurikuler berbasis projek yang dirancang untuk menguatkan upaya pencapaian kompetensi dan karakter sesuai dengan profil pelajar pancasila yang disusun berdasarkan standart kompetensi lulusan. Dengan adanya program baru, perlu adanya peninjauan terkait hasil pengimplemetasian P5 dari dari sudut mata pelajaran tertentu yakni ilmu pengetahuan alam. Seperti halnya, yang pelaksanaan p5 di mts negeri 2 jember yang maasih tergolong asing dan baru saja diberlakukan. Dengan observasi, mengamati kejadian, mewawancarai pihak terkait, maka hasil yang diharapkan pun juga dapat bermanfaat dalam pembelajaran berikutnya. Semua tahapan telah dilaksanakan dengan baik, sehingga dapat disimpulkan bahwa kegiatan pengabdian ini berhasil meningkatkan kompetensi guru dalam melaksanakan proyek penguatan profil pelajar Pancasila. Proyek ini mencakup pemahaman, perancangan, dokumentasi, pelaporan, serta evaluasi dan tindak lanjut dengan hasil yang memuaskan.